Compressing large neural networks : Algorithms, systems and scaling laws - Frantar, Elias
Large language models (LLMs) have made tremendous progress in the past few years, from being able to generate coherent text to matching or surpassing humans in a wide variety of creative, knowledge or reasoning tasks. Much of this can be attributed to massively increased scale, both in the size of the model as well as the amount of training data, from 100s of millions to 100s of billions, or even trillions. This trend is expected to continue, which, although exciting, also raises major practical concerns. Already today's 100+ billion parameter LLMs require top-of-the-line hardware just to run. Hence, it is clear that sustaining these developments will require significant efficiency advances. Historically, one of the most practical ways of improving model efficiency has been compression, especially in the form of sparsity or quantization. While this has been studied extensively in the past, existing accurate methods are all designed for models around 100 million parameters; scaling them up to ones literally 1000x larger is highly challenging. In this thesis, we introduce a new unified sparsification and quantization approach OBC, which through additional algorithmic enhancements leads to GPTQ and SparseGPT, the first techniques fast and accurate enough to compress 100+ billion parameter models to 4- or even 3-bit precision and 50% weight-sparsity, respectively. Additionally, we show how weight-only quantizion does not just bring space savings but also up to 4.5x faster generation speed, via custom GPU kernels. In fact, we show for the first time that it is possible to develop an FP16 times INT4 mixed-precision matrix multiplication kernel, called Marlin, which comes close to simultaneously maximizing both memory and compute utilization, making weight-only quantization highly practical even for multi-user serving. Further, we demonstrate that GPTQ can be scaled to widely overparametrized trillion-parameter models, where extreme sub-1-bit compression rates can be achieved without any inference slow-down, by co-designing a bespoke entropy coding scheme together with an efficient kernel. Finally, we also study compression from the perspective of someone with access to massive amounts of compute resources for training large models completely from scratch. Here the key questions evolve around the joint scaling behavior between compression, model size, and amount of training data used. Based on extensive experimental results for both vision and text models, we introduce the first scaling law which accurately captures the relationship between weight-sparsity, number of non-zero weights and data. This further allows us to characterize the optimal sparsity, which we find to increase the longer a fixed cost model is being trained. Overall, this thesis presents contributions to three different angles of large model efficiency: affordable but accurate algorithms, highly efficient systems implementations, and fundamental scaling laws for compressed training.

Bilateral interactions of optic-flow sensitive neurons coordinate course control in flies - Satapathy, Roshan K; Jösch, Maximilian A; Symonova, Olga; Pokusaeva, Victoria
Behavioural data for Pokusaeva, Satapathy et al. Relevant information can be found in the 'README.txt' file.
Keywords: drosophila; behaviour; locomotion; gap junctions

Communication-efficient distributed training of deep neural networks : An algorithms and systems perspective - Markov, Ilia
Deep learning is essential in numerous applications nowadays, with many recent advancements made possible by training very large models. Despite their broad applicability, training neural networks is often time-intensive, and it is usually impractical to manage large models and datasets on a single machine. To address these issues, distributed deep learning training has become increasingly important. However, distributed training requires synchronization among nodes, and the mini-batch stochastic gradient descent algorithm places a significant load on network connections. A possible solution to tackle the synchronization bottleneck is to reduce a message size by lossy compression. In this thesis, we investigate systems and algorithmic approaches to communication compression during training. From the systems perspective, we demonstrate that a common approach of expensive hardware overprovisioning can be replaced through a thorough system design. We introduce a framework that introduces efficient software support for compressed communication in machine learning applications, applicable to both multi-GPU single-node training and larger-scale multi-node training. Our framework integrates with popular ML frameworks, providing up to 3x speedups for multi-GPU nodes based on commodity hardware and order-of-magnitude improvements in the multi-node setting, with negligible impact on accuracy. Also, we consider an application of our framework to different communication schemes, such as Fully Sharded Data Parallel. We provide strong convergence guarantees for the compression in such a setup. Empirical validation shows that our method preserves model accuracy for GPT-family models with up to 1.3 billion parameters, while completely removing the communication bottlenecks of non-compressed alternatives, providing up to 2.2x speedups end-to-end. From the algorithmic side, we propose a general framework that dynamically adjusts the degree of compression across a model's layers during training. This approach enhances overall compression and results in significant speedups without compromising accuracy. Our algorithm utilizes an adaptive algorithm that automatically selects the optimal compression parameters for model layers, ensuring the best compression ratio while adhering to an error constraint. Our method is effective across all existing families of compression methods. It achieves up to 2.5x faster training and up to a 5x improvement in compression compared to efficient implementations of current approaches. Additionally, LGreCo can complement existing adaptive algorithms.

Many-body entropies and entanglement from polynomially many local measurements - Vermersch, Benoît; Ljubotina, Marko; Cirac, J. Ignacio; Zoller, Peter; Serbyn, Maksym; Piroli, Lorenzo (Physical Review X)
Estimating global properties of many-body quantum systems such as entropy or bipartite entanglement is a notoriously difficult task, typically requiring a number of measurements or classical postprocessing resources growing exponentially in the system size. In this work, we address the problem of estimating global entropies and mixed-state entanglement via partial-transposed (PT) moments and show that efficient estimation strategies exist under the assumption that all the spatial correlation lengths are finite. Focusing on one-dimensional systems, we identify a set of approximate factorization conditions (AFCs) on the system density matrix, which allow us to reconstruct entropies and PT moments from information on local subsystems. This identification yields a simple and efficient strategy for entropy and entanglement estimation. Our method could be implemented in different ways, depending on how information on local subsystems is extracted. Focusing on randomized measurements providing a practical and common measurement scheme, we prove that our protocol requires only polynomially many measurements and postprocessing operations, assuming that the state to be measured satisfies the AFCs. We prove that the AFCs hold for finite-depth quantum-circuit states and translation-invariant matrix-product density operators and provide numerical evidence that they are satisfied in more general, physically interesting cases, including thermal states of local Hamiltonians. We argue that our method could be practically useful to detect bipartite mixed-state entanglement for large numbers of qubits available in today’s quantum platforms.

Anti-plasmid immunity: A key to pathogen success? - Bravo, Jack Peter Kelly (Future Microbiology)

RefinedRust: A type system for high-assurance verification of rust programs - Gäher, Lennard; Sammler, Michael Joachim; Jung, Ralf; Krebbers, Robbert; Dreyer, Derek (Proceedings of the ACM on Programming Languages)
Rust is a modern systems programming language whose ownership-based type system statically guarantees memory safety, making it particularly well-suited to the domain of safety-critical systems. In recent years, a wellspring of automated deductive verification tools have emerged for establishing functional correctness of Rust code. However, none of the previous tools produce foundational proofs (machine-checkable in a general-purpose proof assistant), and all of them are restricted to the safe fragment of Rust. This is a problem because the vast majority of Rust programs make use of unsafe code at critical points, such as in the implementation of widely-used APIs. We propose RefinedRust, a refinement type system—proven sound in the Coq proof assistant—with the goal of establishing foundational semi-automated functional correctness verification of both safe and unsafe Rust code. We have developed a prototype verification tool implementing RefinedRust. Our tool translates Rust code (with user annotations) into a model of Rust embedded in Coq, and then checks its adherence to the RefinedRust type system using separation logic automation in Coq. All proofs generated by RefinedRust are checked by the Coq proof assistant, so the automation and type system do not have to be trusted. We evaluate the effectiveness of RefinedRust by verifying a variant of Rust’s Vec implementation that involves intricate reasoning about unsafe pointer-manipulating code.

Quiver: Guided abductive inference of separation logic specifications in coq - Spies, Simon; Gäher, Lennard; Sammler, Michael Joachim; Dreyer, Derek (Proceedings of the ACM on Programming Languages)
Over the past two decades, there has been a great deal of progress on verification of full functional correctness of programs using separation logic, sometimes even producing “foundational” proofs in proof assistants like Coq. Unfortunately, even though existing approaches to this problem provide significant support for automated verification, they still incur a significant specification overhead: the user must supply the specification against which the program is verified, and the specification may be long, complex, or tedious to formulate. In this paper, we introduce Quiver, the first technique for inferring functional correctness specifications in separation logic while simultaneously verifying foundationally that they are correct. To guide Quiver towards the final specification, we take hints from the user in the form of a specification sketch, and then complete the sketch using inference. To do so, Quiver introduces a new abductive deductive verification technique, which integrates ideas from abductive inference (for specification inference) together with deductive separation logic automation (for foundational verification). The result is that users have to provide some guidance, but significantly less than with traditional deductive verification techniques based on separation logic. We have evaluated Quiver on a range of case studies, including code from popular open-source libraries.

NuSTAR observations of candidate subparsec binary supermassive black holes - Saade, M. Lynne; Brightman, Murray; Stern, Daniel; Connor, Thomas; Djorgovski, S. G.; D’Orazio, Daniel J.; Ford, K. E. S.; Graham, Matthew J.; Haiman, Zoltán; Jun, Hyunsung D.; Kammoun, Elias; Kraft, Ralph P.; et al. (The Astrophysical Journal)
We present an analysis of NuSTAR X-ray observations of three active galactic nuclei (AGN) that were identified as candidate subparsec binary supermassive black hole (SMBH) systems in the Catalina Real-Time Transient Survey based on apparent periodicity in their optical light curves. Simulations predict that close-separation accreting SMBH binaries will have different X-ray spectra than single accreting SMBHs. We previously observed these AGN with Chandra and found no differences between their low-energy X-ray properties and the larger AGN population. However, some models predict differences to be more prominent at energies higher than probed by Chandra. We find that even at the higher energies probed by NuSTAR, the spectra of these AGN are indistinguishable from the larger AGN population. This could rule out models predicting large differences in the X-ray spectra in the NuSTAR bands. Alternatively, it might mean that these three AGN are not binary SMBHs.

Shock cooling and breakout emission for optical flares associated with gravitational-wave events - Tagawa, Hiromichi; Kimura, Shigeo S; Haiman, Zoltán; Perna, Rosalba; Bartos, Imre (The Astrophysical Journal)
The astrophysical origin of stellar-mass black hole (BH) mergers discovered through gravitational waves (GWs) is widely debated. Mergers in the disks of active galactic nuclei (AGNs) represent promising environments for at least a fraction of these events, with possible observational clues in the GW data. An additional clue to unveil AGN merger environments is provided by possible electromagnetic emission from postmerger accreting BHs. Associated with BH mergers in AGN disks, emission from shocks emerging around jets launched by accreting merger remnants is expected. Here we compute the properties of the emission produced during breakout and the subsequent adiabatic expansion phase of the shocks, and we then apply this model to optical flares suggested to be possibly associated with GW events. We find that the majority of the reported flares can be explained by breakout and shock cooling emission. If the optical flares are produced by shock cooling emission, they would display moderate color evolution, possibly color variations among different events, and a positive correlation between delay time and flare duration and would be preceded by breakout emission in X-rays. If the breakout emission dominates the observed lightcurve, we predict the color to be distributed in a narrow range in the optical band and the delay time from GW to electromagnetic emission to be longer than ∼2 days. Hence, further explorations of delay time distributions, flare color evolution, and associated X-ray emission will be useful to test the proposed emission model for the observed flares.

Diagnosing the massive-seed pathway to high-redshift black holes: statistics of the evolving black hole to host galaxy mass ratio - Scoggins, Matthew T; Haiman, Zoltán (Monthly Notices of the Royal Astronomical Society)
Supermassive black holes (SMBHs) with masses of ∼109 M⊙ within the first billion year of the universe challenge our conventional understanding of black hole formation and growth. One pathway to these SMBHs proposes that supermassive stars born in pristine atomic cooling haloes yield massive seed BHs evolving to these early SMBHs. This scenario leads to an overly massive BH galaxy (OMBG), in which the BH to stellar mass ratio is initially Mbh/M* ≥ 1, well in excess of the typical values of ∼10−3 at low redshifts. Previously, we have investigated two massive seed BH candidates from the Renaissance simulation and found that they remain outliers on the Mbh–M* relation until the OMBG merges with a much more massive halo at z = 8. In this work, we use Monte-Carlo merger trees to investigate the evolution of the Mbh–M* relation for 50 000 protogalaxies hosting massive BH seeds, across 10 000 trees that merge into a 1012 M⊙ halo at z = 6. We find that up to 60 per cent (depending on growth parameters) of these OMBGs remain strong outliers for several 100 Myr, down to redshifts detectable with JWST and with sensitive X-ray telescopes. This represents a way to diagnose the massive-seed formation pathway for early SMBHs. We expect to find ∼0.1–1 of these objects per JWST Near Infrared Camera (NIRCam) field per unit redshift at z ≳ 6. Recently detected SMBHs with masses of ∼107 M⊙ and low-inferred stellar-mass hosts may be examples of this population.

Self-lensing flares from black hole binaries: General-relativistic ray tracing of circumbinary accretion simulations - Krauth, Luke Major; Davelaar, Jordy; Haiman, Zoltán; Westernacher-Schneider, John Ryan; Zrake, Jonathan; MacFadyen, Andrew (Physical Review D)
Self-lensing flares (SLFs) are expected to be produced once or twice per orbit by an accreting massive black hole binary (MBHB), if the eclipsing MBHBs are observed close to edge-on. SLFs can provide valuable electromagnetic (EM) signatures to accompany the gravitational waves (GWs) detectable by the upcoming Laser Interferometer Space Antenna (LISA). EM follow-ups are crucial for, e.g., sky-localization, and constraining the Hubble constant and the graviton mass. We use high-resolution two-dimensional viscous hydrodynamical simulations of a circumbinary disk (CBD) embedding a MBHB. We then use very high-cadence output of these hydrodynamical simulation inputs for a general-relativistic ray-tracing code to produce synthetic spectra and phase-folded light curves. Our main results show a significant periodic amplification of the flux with the characteristic shape of a sharp flare with a central dip, as the foreground black hole (BH) transits across the minidisk and shadow of the background BH, respectively. These corroborate previous conclusions based on the microlensing approximation and analytical toy models of the emission geometry. We also find that at lower inclinations, without some occlusion of the minidisk emission by the CBD, shocks from quasi-periodic mass-trading between the minidisks can produce bright flares which can mimic SLFs and could hinder their identification.

Eccentric minidisks in accreting binaries - Westernacher-Schneider, John Ryan; Zrake, Jonathan; MacFadyen, Andrew; Haiman, Zoltán (The Astrophysical Journal)
We show that gas disks around the components of an orbiting binary system (so-called minidisks) may be susceptible to a resonant instability that causes the minidisks to become significantly eccentric. Eccentricity is injected by, and also induces, regular impacts between the minidisks at roughly the orbital period of the binary. Such eccentric minidisks are seen in vertically integrated, two-dimensional simulations of a circular, equal-mass binary accreting from a circumbinary gas disk with a Γ-law equation of state. Minidisk eccentricity is suppressed by the use of an isothermal equation of state. However, the instability still operates and can be revealed in a minimal disk-binary simulation by removing the circumbinary disk and feeding the minidisks from the component positions. Minidisk eccentricity is also suppressed when the gravitational softening length is large (≳4% of the binary semimajor axis), suggesting that its absence could be an artifact of widely adopted numerical approximations; a follow-up study in three dimensions with well-resolved, geometrically thin minidisks (aspect ratios ≲0.02) may be needed to assess whether eccentric minidisks can occur in real astrophysical environments. If they can, the electromagnetic signature may be important for discriminating between binary and single black hole scenarios for quasiperiodic oscillations in active galactic nuclei; in turn, this might aid in targeted searches with pulsar timing arrays for individual supermassive black hole binary sources of low-frequency gravitational waves.

“Tidal Peeling Events”: Low-eccentricity tidal disruption of a star by a stellar-mass black hole - Xin, Chengcheng; Haiman, Zoltán; Perna, Rosalba; Wang, Yihan; Ryu, Taeho (The Astrophysical Journal)
Close encounters between stellar-mass black holes (BHs) and stars occur frequently in dense star clusters and in the disks of active galactic nuclei. Recent studies have shown that in highly eccentric close encounters, the star can be tidally disrupted by the BH in a microtidal disruption event (microTDE), resulting in rapid mass accretion and possibly bright electromagnetic signatures. Here we consider a scenario in which the star might approach the stellar-mass BH in a gradual, nearly circular inspiral, under the influence of dynamical friction in a circum-binary gas disk or three-body interactions in a star cluster. We perform hydrodynamics simulations of this scenario using the smoothed particle hydrodynamics code PHANTOM. We find that under certain circumstances (for initial eccentricity e0 ≳ 0.4 and penetration factor β = 1, or e0 < 0.4 and β ≲ 0.67), the mass of the star is slowly stripped away by the BH. We call this gradual tidal disruption a "tidal-peeling event." Additionally, we discover that some low-eccentricity microTDEs (e0 < 0.4 and β = 1) are a new form of fast luminous transients similar to parabolic microTDEs. Depending on the initial distance and eccentricity of the encounter, these low-eccentricity microTDEs might exhibit significant accretion rates and orbital evolution distinct from those of a typical (eccentric) microTDE.

QuAK: Quantitative Automata Kit - Chalupa, Marek; Henzinger, Thomas A; Mazzocchi, Nicolas Adrien; Sarac, Naci E (12th International Symposium on Leveraging Applications of Formal Methods, Verification and Validation)
System behaviors are traditionally evaluated through binary classifications of correctness, which do not suffice for properties involving quantitative aspects of systems and executions. Quantitative automata offer a more nuanced approach, mapping each execution to a real number by incorporating weighted transitions and value functions generalizing acceptance conditions. In this paper, we introduce QuAK, the first tool designed to automate the analysis of quantitative automata. QuAK currently supports a variety of quantitative automaton types, including Inf, Sup, LimInf, LimSup, LimInfAvg, and LimSupAvg automata, and implements decision procedures for problems such as emptiness, universality, inclusion, equivalence, as well as for checking whether an automaton is safe, live, or constant. Additionally, QuAK is able to compute extremal values when possible, construct safety-liveness decompositions, and monitor system behaviors. We demonstrate the effectiveness of QuAK through experiments focusing on the inclusion, constant-function check, and monitoring problems.

Divergence of separated nets with respect to displacement equivalence - Dymond, Michael; Kaluza, Vojtech (Geometriae Dedicata)
We introduce a hierachy of equivalence relations on the set of separated nets of a given Euclidean space, indexed by concave increasing functions ϕ:(0,∞)→(0,∞). Two separated nets are called ϕ-displacement equivalent if, roughly speaking, there is a bijection between them which, for large radii R, displaces points of norm at most R by something of order at most ϕ(R). We show that the spectrum of ϕ-displacement equivalence spans from the established notion of bounded displacement equivalence, which corresponds to bounded ϕ, to the indiscrete equivalence relation, coresponding to ϕ(R)∈Ω(R), in which all separated nets are equivalent. In between the two ends of this spectrum, the notions of ϕ-displacement equivalence are shown to be pairwise distinct with respect to the asymptotic classes of ϕ(R) for R→∞. We further undertake a comparison of our notion of ϕ-displacement equivalence with previously studied relations on separated nets. Particular attention is given to the interaction of the notions of ϕ-displacement equivalence with that of bilipschitz equivalence.

Duality theory in linear optimization and its extensions -- formally verified - Dvorak, Martin; Kolmogorov, Vladimir (arXiv)
Farkas established that a system of linear inequalities has a solution if and only if we cannot obtain a contradiction by taking a linear combination of the inequalities. We state and formally prove several Farkas-like theorems over linearly ordered fields in Lean 4. Furthermore, we extend duality theory to the case when some coefficients are allowed to take "infinite values".
Keywords: Farkas lemma; linear programming; extended reals; calculus of inductive constructions

Structural characterization of spumavirus capsid assemblies - Porley, Dario J
The Retroviridae family consists of two sub-families, the Orthoretrovirinae and the Spumaretrovirinae. The Orthoretroviruses contain important human pathogens, such as the human immunodeficiency virus 1 (HIV-1). They also harbor other retrovirus species which are regularly used as model systems to study the retroviral life cycle. The main structural component of the retroviruses, is the Gag protein and its truncation derivatives occurring during viral maturation. Orthoretroviral Gag assemblies have been extensively studied to understand the interactions that confer stability and morphology to viral particles. The Spumaretrovirinae subfamily represent an early diverging branch of the Retroviridae. Its members, the Foamy viruses (FV), share most of the conventional features found in retroviruses. However, they also possess multiple characteristics that make them unique. In particular, FV Gag does not get extensively cleaved as in orthoretroviruses. Hence, the Gag architecture deviates from the canonical domain arrangement in FV. They also exhibit a peculiar particle morphology, having no apparent immature state and a seemingly icosahedral mature particle. Due to this, many fundamental questions on FV structural assembly mechanisms remain open. To answer these questions, was the main focus of this thesis. Mainly, it is not known how FV assemble their core in a virus particle and what are the important assembly interaction sites within said core. What is the minimum assembly competent domain of FV Gag? Is there a morphological change in the assembly type of FVGag lattices? If so, what is defining these morphological shifts? Finally, it would be interesting to know what is the evolutionary relationship between FV and the rest of the retrotranscribing elements, from a structural point of view? To answer these questions, membrane-enveloped mammalian cell-derived FV virus-like particles (VLPs) were produced. Cryo-electron tomography (cryo-ET) analysis suggested these FV VLPs do not form a canonical retroviral Gag lattice structure, which is in line with earlier observations. To further evaluate FV Gag assembly competence and morphology, the first bacterial cell-derived in vitro VLP assembly system was designed and optimized. Using this system with different truncation variants, the minimum assembly competent domain of FV Gag was found to be the putative CA300-477 domain. Varying VLP morphologies were also observed and strongly suggested residues upstream of CA300-477 play a role in morphology determination. Finally, a combined cryo-electron microscopy (cryoEM) and cryo-ET approach was taken to analyze tubular assemblies from the minimal assembly competent domain. This revealed an unexpectedly unique non-canonical assembly architecture. Three novel lattice stabilizing interfaces were described which proved to be as unique as the lattice arrangement. Comparison to a newly published FV CA core structure revealed the CA-CA interactions in the atypical assembly do not recapitulate what is described for the FV core lattice. However, the new in vitro VLP assembly system obtained in this thesis also provides an exciting opportunity to study still unresolved FV assembly features in a potentially facilitated approach compared to conventional methods. In summary, this work provided a deeper understanding of the basic FV Gag assembly unit, as well as presenting the first FV Gag-derived in vitro VLP assembly system. This system reveals a novel and unique assembly architecture among retroviral in vitro assemblies.

Biochemical and structural insights into ADAR1 RNA editing - Kaczmarek, Beata M
ADAR1 is broadly expressed across various tissues and is vital in regulating pathways associated with innate immune responses. ADAR1 marks double-stranded RNA as "self" through its A-to-I editing activity, effectively repressing autoimmunity and maintaining immune tolerance. This editing process has been detected at millions of sites across the human genome. However, the mechanism underlying ADAR1's substrate selectivity properties remains largely unclear, with much of the current knowledge derived from comparisons to its more extensively studied homolog, ADAR2. By studying ADAR1 in complex with its RNA substrates and applying a combination of biochemical techniques and structural studies using CryoEM, we aim to gain a more comprehensive understanding of the substrate selectivity characteristics of ADAR1. In this thesis, the purification protocol for ADAR1 was successfully optimized, resulting in the first report in the literature to achieve high protein purity and activity. This advancement enabled the investigation of complex formation between ADAR1 and various RNA substrates, leading to the identification of optimal conditions for preparing the cryoEM sample. However, despite comprehensive optimization of the cryo-EM conditions, the resulting data lacked the desired quality, highlighting the need for similar rigorous optimization of the RNA substrates to facilitate structural studies of the ADAR1-RNA complex. The study was complemented by AlphaFold predictions, which provided some insights into this mechanism. Moreover, during this project I established a collaboration with a research group focused on studying ADAR homologs. Notably ADAR homologs were identified in bivalve species, and it was further demonstrated that ADAR and its A-to-I editing activity are upregulated in Pacific oysters during infections with Ostreid herpesvirus-1—a highly infectious virus that leads to significant losses in oyster populations globally. I successfully purified oyster ADAR and prepared in vitro edited RNA for nanopore sequencing—a direct sequencing technology capable of detecting modified nucleotides without the need for reverse transcription. The collaborators initiated optimization of this nanopore-based approach. However, current technological limitations still constrain the reliable detection of modified nucleotides. The project also examined the impact of RNA editing on RNA binding and filament formation by MDA5, a key cytosolic dsRNA sensor that triggers an interferon response. A primary target of ADAR1's editing activity is RNA derived from repetitive elements present in the genome, particularly Alu elements forming double-stranded RNA. When unedited, these RNA sequences are recognized by MDA5. However, the mechanisms by which MDA5 interacts with Alu RNAs, as well as the role of A-to-I editing in influencing this binding, are still not well understood. The interaction between MDA5 and Alu elements, was successfully established. This was achieved through the testing of different RNA variants and the evaluation of filament formation using binding techniques and electron microscopy imaging. This groundwork has set the conditions for further evaluation using CryoEM. Furthermore, the effects of A-to-I editing on the binding properties of MDA5 with Alu RNA were investigated. Given the recent research that has provided new insights into MDA5's interaction with dsRNA, it is essential to revise the experimental setup to integrate these findings before moving forward with the CryoEM sample analysis.

Strong charge-photon coupling in Germanium enabled by granular aluminium superinductors - Janik, Marian
State-of-the-art quantum computers, with roughly a thousand qubits, face a crucial technological challenge of scaling up. Spins confined in quantum dots (QDs) are a promising candidate for qubits due to their long coherence, tunability, control, and readout. However, their natural coupling is the short-ranged (∼ 100 nm) exchange interaction, limited to nearest neighbours. Long-ranged (∼ 1 mm) qubit interactions mediated by a photon could be engineered through a coherent spin-photon coupling. Achieving a strong coupling to a photon is inherently challenging in QDs due to the small dipole moment of the confined charge. However, the potential of high-impedance resonators to compensate for this has gained significant attention in the past decade. Nevertheless, previous QD circuit quantum electrodynamics implementations have not exceeded the impedance of ∼ 3.8 kΩ, leaving opportunities for significant improvement. The large kinetic inductance of granular aluminium (grAl) could provide an order-of-magnitude enhancement. However, fully exploiting the potential of disordered or granular superconductors is challenging as their impedances close to the superconductor-to-insulator transition are difficult to control reproducibly. We report on the realization of a wireless ohmmeter which allows in situ resistance measurements during film deposition and, therefore, indirect control of the kinetic inductance of grAl films. This allows us to reproducibly fabricate resonators with characteristic impedance exceeding the resistance quantum, even reaching 22.3 kW, due to the large sheet kinetic inductance of up to 3 nH □−1 . By integrating an 8 kW resonator with a germanium double QD, we demonstrate a strong charge-photon coupling with the highest rate reported, 566 MHz. The demonstrated method and grAl properties make these resonators suitable for boosting the spin-photon coupling strength, a crucial requirement for fast, high-fidelity, long-distance two-qubit gates.

Thermal effects in one dimensional Josephson chains - Mukhopadhyay, Soham
This work can be broadly classified into the study of critical phenomena in a one dimensional array of Josephson junctions. While we study quantum criticality when the array is in thermal equilibrium at zero bias, the non-equilibrium study involves understanding the bistability of the array at a critical non-zero bias. This work furthers our knowledge in understanding quantum critical behaviour at finite temperatures in a one dimensional Josephson array, while also establishing relaxation behaviour dual to that observed in a single Josephson junction. Chapter 1 briefly introduces the model to understand superconductor-insulator phase transition in a one dimensional Josephson array and points out the state of the field from where we started our zero-bias experiments. In this context it discusses the phase-charge duality observed in a Josephson array and its dual hysteretic behaviour to that of a single junction, setting the ground for our non-equilibrium study of the array. Chapter 2 shows the experimental setup and the chip layout of the device we measured. In chapter 3 we show that, unlike the typical quantum-critical broadening scenario, in one dimensional Josephson arrays temperature dramatically shifts the critical region. This shift leads to a regime of superconductivity at high temperature, arising from the melted zero-temperature insulator. Our results quantitatively explain the low-temperature onset of superconductivity in nominally insulating regimes, and the transition to the strongly insulating phase. We further present, to our knowledge, the first understanding of the onset of anomalous-metallic resistance saturation [30]. This work demonstrates a non-trivial interplay between thermal effects and quantum criticality. A practical consequence is that, counterintuitively, the coherence of high-impedance quantum circuits is expected to be stabilized by thermal fluctuations. In chapter 4, we show relaxation oscillations in a current-biased one dimensional array of Josephson junctions. These oscillations are well described by a circuit model, dual to the ordinary Josephson relaxation oscillations [72]. Injection locking these oscillations results in current plateaux. The relaxation step is found to obey a characteristic self-consistent relation, suggesting that it is governed by overheating effects. Chapter 5 describes the various checks and analysis we performed to support our conclusions made in chapters 3 and 4. Finally, chapter 6 describes the nanofabrication steps and the finite element electromagnetic simulations we performed to fabricate our devices.